ANALYSIS OF UROLOGICAL MORBIDITY IN THE ADULT POPULATION MOSCOW FOR THE YEARS 2006-2015 - Ашот Рафаэлович Геворкян (Медицина в Кузбассе)
The article, based on the materials of the official statistical reporting for 2006-2015, analyzed the trends of the urological diseases of the adult population of Moscow, compared with the Russian Federation. It is established, diseases of the genitourinary system (GUS) consistently occupy the third place in the structure incidence and fourth place in the adult morbidity structure of the population of Moscow and the Russian Federation. In2015, inMoscow, their share was 7,6 % among new cases of disease and 8,7 % of all diseases registered among the adult population.